Intermedial Figures between Theater and Cinema. The Transposition to the Screen of Abelardo Estorino’s La casa vieja - Moreno del Cristo, Aluned (2025)
Introduction: Film adaptations created from plays have become a favorable area to examine the intermedial and transdisciplinary relationships between both artistic practices. Objective: This paper aims to analyze the intermedial relationships that can be found between La casa vieja, a play by Cuban Abelardo Estorino, and Casa vieja, its film version, by the Cuban Lester Hamlet, in order to investigate the productivity of the dialogue that occurs between theater and cinema. Methods: We have developed a comparative analysis among some relevant elements of both works, which allow us to establish connections and find differences between the two examined artistic mediums. Results: In a general sense, it is possible to establish that, in the film, a transposition of the play is carried out, through which Estorino’s piece is rewritten, giving it new meanings. Conclusions: In Casa vieja, it is possible to find the presence of different procedures and intermedial figures, which allow us to appreciate the film’s reevaluation of the play, as well as the productivity of updating and transposing it to a new context and different medium. The marks of theatricality within the movie also make it possible to reflect on the conflicts and social problems raised through its plot.